LANGUAGE LEARNING MEDIA THROUGH READING SPEECH FOR THE DEAF BASED ON ANDROID - Muhammad Hafizulloh; Lalu Puji Indra Kharisma; Nurnadiyah Syuhada; Qurratul Aini (Universitas Islam Negeri Mataram, 2024)
The communication system for the deaf is non-verbal (non-verbal) communication using gestures, either with hand gestures or body gestures and facial expressions. Deafness can be interpreted as a state of hearing loss. Deaf children are children who experience hearing deficiencies so that they require special services. Deaf children have difficulty in observing sounds through their hearing, therefore they must capture sounds or voices or expressions of someone through their sight. In this study, the author examines and analyzes the problem of language learning media through reading speech for the deaf based on Android. The purpose of writing is as an aid or alternative media to be able to learn how to read the opponent's lip movements in the communication process. This application uses the research and development (R&D) method and in designing this learning media application, it uses the ADDIE Model (Analysis, Design, Development, Implementation, and Evaluation). The results of this study are that the application of language learning media through reading speech for the deaf based on Android that has been created can help the learning process, especially between teachers and deaf students in learning at SLB Muhammadiyah Kelayu